San Carlos City a celebration - Garcia, Fe Casillan 1936-; Namnama, Hidalgo P. ([Pangasinan] M. Casillan, 2005)
"San Carlos City : A Celebration portrays the significant, diverse, and artistic events in the past and present lives of the Pangasinenses of San Carlos City. It covers many aspects including the forgotten experiences of many folk in the city and the barrios. The book in an offshoot of a brief research project to uncover the real psyche of San Carlenians, young and old alike. The output consists of insights about people, worldviews, and things. This book documents through text, images, music, and photographs San Carlos City's cultural legacy, its people, its rich history, and unique environment. In its pages, readers may come across situations and things that they hold close to their hearts even if many of the episodes come from the author's very personal perceptions."--Preface.
Part I. Lest you forget San Carlos City -- Onward San Carlos City -- Time travel -- Blast from the past -- New beginnings -- La dolce vita -- Personalities -- Moving around -- School daze -- Education in San Carlos -- Religion : God have mercy -- Working hard -- Life in the barrio -- Fiesta time -- Party! -- Who is the San Carlenian? -- Part II. San Carlos City music memorabilia -- Part III. A celebration of families -- Postscript -- Selected bibliography -- About the author -- Cover story.
Keywords: Songs -- Philippines -- Pangasinan; Family -- Philippines -- Pangasinan